Convergence theorems for I-nonexpansive mapping - B. E. Rhoades; Seyit Temir (International Journal of Mathematics and Mathematical Sciences)
We establish the weak convergence of a sequence of Mann iterates of an I-nonexpansive map in a Banach space which satisfies Opial's condition.